2021
DOI: 10.1097/mot.0000000000000946
|View full text |Cite
|
Sign up to set email alerts
|

The use of marginal kidneys in dual kidney transplantation to expand kidney graft utilization

Abstract: Purpose of reviewThe purpose of this review is to chronicle the history of dual kidney transplantation (DKT) and identify opportunities to improve utilization of marginal deceased donor (MDD) kidneys through DKT. Recent findingsThe practice of DKT from adult MDDs dates back to the mid-1990s, at which time the primary indication was projected insufficient nephron mass from older donors. Multiple subsequent studies of short-and longterm success have been reported focusing on three major aspects: Identifying appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…Despite the application of expanded criteria, deceased donors or marginal kidneys in dual kidney procedures (36 , 37) , it has been calculated that fewer than 25% of the waitlisted patients are transplanted because of organ shortage ( 38 ). To overcome the chronic organ shortage, kidney donation is routinely performed in one-third of patients from living donors.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the application of expanded criteria, deceased donors or marginal kidneys in dual kidney procedures (36 , 37) , it has been calculated that fewer than 25% of the waitlisted patients are transplanted because of organ shortage ( 38 ). To overcome the chronic organ shortage, kidney donation is routinely performed in one-third of patients from living donors.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, as 40% of the renal transplants performed in the Unite States are DCD renal transplants, alternative, more effective approaches that may improve the function and the overall outcome of "less than optimal graft" are urgently needed. Our transplant program has a broad, longstanding experience in the use of such allografts including DCD kidneys [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] and our patients would see potential benefit from treatments that mitigate DCD kidney damage. Overall, our ex vivo data confirmed the beneficial effects of MITO observed in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…We as a community have a good understanding of the phenotype of “hard to place” deceased donor kidneys (Table 1), yet we continue to promote a “one size fits all” approach to organ allocation and distribution 17–19 . For example, when the “new” UNOS dual kidney allocation policy was implemented in September 2019, the data demonstrated that when either the donor age was ≥68 years or the KDPI was ≥92%, then the kidney discard rate surpassed the rate of single kidney utilization 20 . We are also aware of the “aggressive center” phenotype (or donor utilization index) and those centers that are most likely to import and utilize MDD kidneys provided they receive the offer in a timely fashion and the offer is an “open” offer (to anyone on the center's waiting list) 17,19,21,22 …”
Section: Opinion/hypothesismentioning
confidence: 99%
“…[17][18][19] For example, when the "new" UNOS dual kidney allocation policy was implemented in September 2019, the data demonstrated that when either the donor age was ≥68 years or the KDPI was ≥92%, then the kidney discard rate surpassed the rate of single kidney utilization. 20 We are also aware of the "aggressive center" phenotype (or donor utilization index) and those centers that are most likely to import and utilize MDD kidneys provided they receive the offer in a timely TA B L E 1 Defining criteria for marginal deceased donor (MDD)/hard to place deceased donor kidneys Pre-recovery criteria:…”
mentioning
confidence: 99%